Religious Learning Environment Psychology, Learning Climate that Supports Religiosity and Islamic Values - Randy Pratama; Mhd Yudha Firmansyah; Muhammad Sanusi; Muhammad Luthfi Anshori; Salmaini Yeli (unprimdn.ac.id, 2025)
This article examines the psychology of religious learning environments and the importance of creating a conducive learning climate for the development of religiosity and Islamic values. The learning environment encompasses not only the physical aspects of the classroom, but also the psychological, social, and spiritual dimensions that shape the learning experience of students. This literature review analyzes theories of environmental psychology, classroom climate, and their application in the context of Islamic education through a review of the latest Indonesian-language literature (2020-2025). The discussion covers the basic concepts of learning environment psychology, components of a religious learning climate, relevant theories (Bronfenbrenner, Bandura, Bloom), characteristics of a learning environment that supports religiosity, and practical strategies for creating an Islamic learning climate. The findings show that a positive, inclusive, and religious learning environment significantly increases learning motivation, psychological well-being, internalization of Islamic values, and the formation of religious character in students. This article concludes that creating a religious learning climate requires synergy between Islamic physical environment design, a strong school culture, teacher competence in creating a safe and supportive psychological atmosphere, and the active involvement of all education stakeholders.